Is a Federal European Constitution for an enlarged European Union necessary? Some preliminary suggestions using public choice analysis - Friedrich G. Schneider (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2009)
In order to guarantee a further successful functioning of the enlarged European Union a Federal European Constitution is proposed. Six basic elements of a future European federal constitution are developed: the European commission should be turned into an European government and the European legislation should consist of a two chamber system with full responsibility over all federal items. Three further key elements are the subsidiarity principle, federalism and the secession right, which are best suited to limiting the domain of the central European authority to which certain tasks are given, such as defense, foreign and environmental policy. Another important feature is direct democracy, which provides the possibility for European voters to participate actively in the political decision making, to break political and interest group cartels, and to prevent an unwanted shifting of responsibilities from EU member states to the European federal level.
Keywords: D72; D78; H7; H11; 330